Longterm Risk of Solid Organ De Novo Malignancies After Liver Transplantation: A French National Study on 11, 226 Patients. Issue 10 (25th October 2018) - Sérée, Olivier; Altieri, Mario; Guillaume, Elodie; De Mil, Rémy; Lobbedez, Thierry; Robinson, Philip; Segol, Philippe; Salamé, Ephrem; Abergel, Armand; Boillot, Olivier; Conti, Filomena; Chazouillères, Olivier; et al.
Abstract : De novo malignancies are one of the major late complications and causes of death after liver transplantation (LT). Using extensive data from the French national Agence de la Biomédecine database, the present study aimed to quantify the risk of solid organ de novo malignancies (excluding nonmelanoma skin cancers) after LT. The incidence of de novo malignancies among all LT patients between 1993 and 2012 was compared with that of the French population, standardized on age, sex, and calendar period (standardized incidence ratio; SIR). Among the 11, 226 LT patients included in the study, 1200 de novo malignancies were diagnosed (10.7%). The risk of death was approximately 2 times higher in patients with de novo malignancy (48.8% versus 24.3%). The SIR for all de novo solid organ malignancies was 2.20 (95% confidence interval [CI], 2.08‐2.33). The risk was higher in men (SIR = 2.23; 95% CI, 2.09‐2.38) and in patients transplanted for alcoholic liver disease (ALD; SIR = 2.89; 95% CI, 2.68‐3.11). The cancers with the highest excess risk were laryngeal (SIR = 7.57; 95% CI, 5.97‐9.48), esophageal (SIR = 4.76; 95% CI, 3.56‐6.24), lung (SIR = 2.56; 95% CI, 2.21‐2.95), and lip‐mouth‐pharynx (SIR = 2.20; 95% CI, 1.72‐2.77). In conclusion, LT recipients have an increased risk of de novo solid organ malignancies, and this is strongly related to ALD as a primary indication for LT. Abstract : Pauline Houssel‐Debry has received travel grants from Astellas and Biotest. Mario Altieri and Jérôme Dumortier had the idea of the project and participated in the analysis and interpretation of data. Olivier Sérée, Elodie Guillaume, Rémy De Mil, Thierry Lobbedez, and Guy Launoy performed statistical analysis of data. Olivier Sérée, Mario Altieri, Philip Robinson, and Jérôme Dumortier participated in the writing of the manuscript. Mario Altieri, Philippe Segol, Ephrem Salamé, Armand Abergel, Olivier Boillot, Filomena Conti, Olivier Chazouillères, Maryline Debette‐Gratien, Dominique Debray, Géraldine Hery, Sébastien Dharancy, François Durand, Christophe Duvoux, Claire Francoz, Jean Gugenheim, Jean Hardwigsen, Pauline Houssel‐Debry, Emmanuel Jacquemin, Nassim Kamar, Marianne Latournerie, Pascal Lebray, Vincent Leroy, Alessandra Mazzola, Martine Neau‐Cransac, Georges‐Philippe Pageaux, Sylvie Radenne, Faouzi Saliba, Didier Samuel, Claire Vanlemmens, Marie‐Lorraine Woehl‐Jaegle, and Jérôme Dumortier were liver transplant center medical managers and approved the final version of the manuscript.